The Importance of the Interaction of CheD with CheC and the Chemoreceptors Compared to Its Enzymatic Activity during Chemotaxis in Bacillus subtilis - Yuan, Wei; Glekas, George D.; Allen, George M.; Walukiewicz, Hanna E.; Rao, Christopher V.; Ordal, George W. (PLOS ONE, 2012)
Bacillus subtilis use three systems for adaptation during chemotaxis. One of these systems involves two interacting proteins, CheC and CheD. CheD binds to the receptors and increases their ability to activate the CheA kinase. CheD also binds CheC, and the strength of this interaction is increased by phosphorylated CheY. CheC is believed to control the binding of CheD to the receptors in response to the levels of phosphorylated CheY. In addition to their role in adaptation, CheC and CheD also have separate enzymatic functions. CheC is a CheY phosphatase and CheD is a receptor deamidase. Previously, we demonstrated that CheC’s phosphatase activity plays a minor role in chemotaxis whereas its ability to bind CheD plays a major one. In the present study, we demonstrate that CheD’s deamidase activity also plays a minor role in chemotaxis whereas its ability to bind CheC plays a major one. In addition, we quantified the interaction between CheC and CheD using surface plasmon resonance. These results suggest that the most important features of CheC and CheD are not their enzymatic activities but rather their roles in adaptation.